Analisis Kesalahan Tata Tulis Bahasa Jawa Pada Siswa Kelas VII MTs AL Muslihun Tlogo Kanigoro - Sari, Dian Nurfita; Setyawan, Bagus Wahyu (Program Studi Pendidikan Bahasa dan Sastra Daerah, 2023)
The purpose of this research is to describe grammatical errors in writing Javanese for grade 7 students and to describe what are the factors that cause errors in writing Javanese letters. This study uses a type of qualitative descriptive research. Test and interview methods were used to collect data. Data analysis in this study used descriptive data analysis and the results showed that there were several grammatical errors in the Javanese language in the form of errors in the use of vowels. Factors causing errors in writing are due to a lack of learning and understanding of Javanese vowels